PENGELOLAAN KELAS DALAM MENINGKATKAN BELAJAR SISWA - Sri Warsono (UNIVERSITAS BENGKULU, 2016)
The purpose of this research is to describe the planning ofclassroom management, the implementation of classroom management, the supervision of classroom management andsupporting and hibiting factors of classroom management in increasing student’s learning results. The method of this research was descriptive qualitative. The results of the reseach show that the planning of classroom management was done by facility, teaching management and student’s arrangement, the implementation of classroom management was done by applying some classroom management principles and some approaches, the supervision has been done continuously, thesupporting and inhibiting factors are physical environment, social emotional and organization condition.Keywords: classroom management, study, students